2020
DOI: 10.1093/nar/gkaa422
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing pre-symptomatic tissue to gain insights into the molecular and mechanistic origins of late-onset degenerative trinucleotide repeat disease

Abstract: Abstract How genetic defects trigger the molecular changes that cause late-onset disease is important for understanding disease progression and therapeutic development. Fuchs’ endothelial corneal dystrophy (FECD) is an RNA-mediated disease caused by a trinucleotide CTG expansion in an intron within the TCF4 gene. The mutant intronic CUG RNA is present at one–two copies per cell, posing a challenge to understand how a rare RNA can cause disease. Late-onset FECD is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
38
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 55 publications
10
38
1
Order By: Relevance
“…The original RNA-seq study by Chu and others concluded that the TCF4 CTG TNR expansion increases the stability and thus the amount of expanded CTG repeat-including intronic RNAs in the corneal endothelium and causes comprehensive changes in splicing. No alterations in the overall expression of mature TCF4 mRNA was noted 28 . The study by Nikitina et al was a data article and no conclusions were made 27 .…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…The original RNA-seq study by Chu and others concluded that the TCF4 CTG TNR expansion increases the stability and thus the amount of expanded CTG repeat-including intronic RNAs in the corneal endothelium and causes comprehensive changes in splicing. No alterations in the overall expression of mature TCF4 mRNA was noted 28 . The study by Nikitina et al was a data article and no conclusions were made 27 .…”
Section: Discussionmentioning
confidence: 90%
“…To describe whether an increased CTG TNR affects the expression of different TCF4 transcripts, we performed a comprehensive analysis of two previously published RNA-seq datasets from the corneal endothelium of FECD patients with an expanded TCF4 CTG TNR and control groups without the repeat expansion 27 , 28 . The 2019 dataset generated by Nikitina et al includes 6 controls and 8 FECD patients with an expanded TCF4 CTG TNR 27 , and the 2020 dataset by Chu et al includes 9 controls and 6 FECD patients with an expanded TCF4 CTG TNR 28 . First, we evaluated how the levels of transcripts beginning from the CTG TNR region change in FECD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations